The influence of the flow velocity of the appearance and performance of gear ambai - Yustian, Sandra; ', Nofrizal; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The purpose of this study is to find the position of fishing gear ambai good. If the goal is reached, this research study is expected to provide benefits for fishermen in the field of the arrest. To determine the shifting and movement ambai good fishing gear, miniature fishing gear ambai in 1:50 scale test into the flume tank with current unit cm / sec. At the current speed of 44.3 cm / sec ambai stable fishing gear, if the current speed exceeds 246.1 cm / sec, ambai fishing gear could be damaged.Keywords: Ambai, current, flum tank